Análise crítica do discurso da sustentabilidade e da representação dos atores sociais em marcas amazônicas - Souza, Jackeline Andrade Duarte de (2022)
In an Amazonian context of environmental degradation, companies find themselves increasingly responsible for adopting measures that demonstrate commitment to social and environmental issues, taking positions beyond the economic. This research intends as a general proposal: To analyze the sustainability discourse, the discursive representation and the visual interaction of social actors in the discourse of Amazonian brands, which present the perspective of advertising discourse. More specifically, we aim to: (1) Investigate how brands discursively approach sustainable development; (2) Analyze the discursive representation of social actors in Amazonian brands; (3) Identify the constitution of visual interaction between image participants. For this purpose, 2 (two) Amazonian brands that operate in the food sector were selected, with a local product, the Amazonian cocoa, a total of 4 (four) visual advertising texts and 4 (four) verbal-visual texts were collected companies' websites and social networks. We take as investigative support the theories and methodologies of Functional Systemic Linguistics, by Halliday (1994); Halliday and Matthiessen (2004/2014), for the Ideational Metafunction, via processes; Fairclough's (2001; 2003) Critical Discourse Analysis for lexicon and nominalization; by the discourse of sustainability, by Sachs (2009), Boff (2012), among others; the Theory of Representation of Social Actors, by van Leeuwen (1996/2008), for the inclusion category; and the Theory of Multimodality in Visual Design Grammar, by Kress and van Leeuwen (1996/2006), for interactive meaning. As results obtained, we noticed that the companies brought sustainability issues to the discussion on their official websites and publications on social networks by highlighting the participants responsible for the chocolate production process, highlighting the commitment and their actions within the Amazon, and by showing how the development of the company favors the environment and the local population. Through the discursive analysis of the representations brought by the brands, we noticed that the social actors have a relationship of involvement, being specified, identified, individualized and named. By investigating the interaction, we observed that the visual representation of the social actors occurs in a direct way, with a proximity, demonstrating a relationship of involvement and equality between the represented participants and the observer of the image. We conclude that while the proposed objectives were achieved, the brands brought environmental, social and economic issues to the forefront, in addition to producing representations with the inclusion of social actors.